Compliant citizens, defiant rebels or neither? Exploring change and complexity in COVID‐19 vaccine attitudes and decisions in Bradford, UK: Findings from a follow‐up qualitative study. (1st December 2022) - Lockyer, Bridget; Moss, Rachael H.; Endacott, Charlotte; Islam, Shahid; Sheard, Laura
Abstract: Background: COVID‐19 vaccines have been the central pillar of the public health response to the pandemic, intended to enable us to 'live with Covid'. It is important to understand change and complexity of COVID‐19 vaccines attitudes and decisions to maximize uptake through an empathetic lens. Objective: To explore the factors that influenced people's COVID‐19 vaccines decisions and how their complex attitudes towards the vaccines had changed in an eventful year. Design and Participants: This is a follow‐up study that took place in Bradford, UK between October 2021 and January 2022, 1 year after the original study. In‐depth phone interviews were conducted with 12 (of the 20 originally interviewed) people from different ethnic groups and areas of Bradford. Reflexive thematic analysis was conducted. Results: Eleven of the 12 participants interviewed had received both doses of the COVID‐19 vaccine and most intended to have a booster dose. Participants described a variety of reasons why they had decided to have the vaccines, including the following: feeling at increased risk at work; protecting family and others in their communities; unrestricted travel and being influenced by the vaccine decisions of family, friends and colleagues. All participants discussed ongoing interaction with COVID‐19 misinformation and for some, this meant they were uneasy about their decision to have the vaccine. They described feeling overloaded by and disengaged from COVID‐19 information, which they often found contradictory and some felt mistrustful of the UK Government's motives and decisions during the pandemic. Conclusions: The majority of participants had managed to navigate an overwhelming amount of circulating COVID‐19 misinformation and chosen to have two or more COVID‐19 vaccines, even if they had been previously said they were unsure. However, these decisions were complicated, demonstrating the continuum of vaccine hesitancy and acceptance. This follow‐up study underlines that vaccine attitudes are changeable and contextual. Patient or Public Contribution: The original study was developed through a rapid community and stakeholder engagement process in 2020. Discussion with the Bradford Council Public Health team and the public through the Bradford COVID‐19 Community Insights Group was undertaken in 2021 to identify important priorities for this follow‐up study.